Direct plant regeneration from node and apex explants of cotton in Turkey - (:unkn) unknown (DIAGNOSIS PRESS LTD, 2001)
The objective of this project is to obtain resistance cotton plants to Verticillum dahliae, which is one of the important diseases of cotton in Turkey. One of the method to improve the resistance against such disease is to genetically engineer plants for the expression of antifungal genes (encoding proteins) that are directly toxic to pathogen of interest. Since regeneration protocols for cotton clones from Turkey has not been reported, a shoot regeneration for two important cotton clones (Nazilli M-503 and Sel-5) was developed and presented here. Shoot regeneration from different explants (leaves, petioles, internodes, nodes, hypocotyl and apex) of cotton was investigated on Murashige and Skoog (MS) medium with appropriate supplements of growth regulators. The highest shoot regeneration efficiency was obtained from the nodes and apex explants on MS11 (MS with 2 mg/l zeatin and 2mg/l kinetin) and MS12 (MS with 2 mg/l BAP and 2mg/l zeatin) respectively. Root formation was obtained on MS supplemented with 0.5 mg/l indolebutyric acid (IBA). This regeneration system can be used for further studies on transformation of cotton with antifungal genes.
Keywords: ANTIMICROBIAL PEPTIDES; RESISTANCE; DEFENSINS